Harmonisasi Hukum Ketenagakerjaan di Kawasan Asean dalam Mendukung Penerapan Asean Mutual Recognition Arrangement (Studi Kasus: Indonesia, Singapore dan Vietnam) - Rediston Sirait; Rina Shahriyani Shahrullah; Elza Syarief (Program Studi Ilmu Hukum Universitas Maritim Raja Ali Haji, 2022)
This study aims to analyze and describe the harmonization of labour law in the ASEAN region, especially Indonesia, Singapore and Vietnam in support of the ASEAN Mutual Recognition Arrangement. This research was conducted by using a normative juridical research method, with a statute approach. The study found that in welcoming the ASEAN Economic Community 2025 as a follow-up to the 2015 ASEAN Economic Community which has ended, the ASEAN member states have agreed to create a regional free market that aims to improve the living standards of the ASEAN community which has implications for the moral awareness of ASEAN member states that must unite in their territory in a free market. The reality of the implementation of the ASEAN Economic Community 2025, specifically regarding the free market for professional services in the region, the ASEAN member states have not moved seriously to implement it, each of the ASEAN member states is still using its country's positive regulations/laws which may lead to a free labour market process in the territory of their respective countries. The harmonization of regulations relating to foreign workers in each positive law of the ASEAN member states is very urgent and necessary, both formal and immaterial form in supporting ASEAN Mutual Recognition Arrangements. So that the vision and purpose of the establishment of the 2015 ASEAN Economic Community which is then followed by the 2025 ASEAN Economic Community are to create a free market and improve the competitiveness of human resources and the quality of human resources so that the creation of an integrated economic area can be achieved.